Development of E Rapport on Child Growth and Development in the Early Childhood Education (PAUD) - Gantini, Dede; Mardiah, Siti Saadah; Patimah, Siti; Rismawan, Wawan (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2023)
Every child has the right to monitor growth and development without exception, carried out at the family level; early detection of irregularities is carried out by trained health workers and early childhood/kindergarten educators. This activity has not yet reached the targeted figure, which is only 59.28% in 2020. Optimization of child growth and development can be developed through Paysandú integrated preschool. Based on this description, the authors consider it necessary to synergize the implementation of the SDIDTK program in the PAUD education program by making growth and development reports. The purpose of developing e-report cards is to increase efficiency and effectiveness and assist teachers, homeroom teachers, cadres, and health workers in managing the SDIDTK program so that valid, practical, and effective digital-based e-report applications can be obtained. Method: The research design refers to the development of the 4D model, including defining, designing, developing, and disseminating. The stages carried out include steps 1, 2, and 3, while step 4 is carried out in the following year. Result: The developed E-report card application is named SIDDIKA (Child health data and information application). The results of the material expert validation scored 73.5% (feasible). Media expert validation results scored 81.5% (very feasible). The test results on the child health data and information application design (SIDDIKA), which was carried out on users in the field, scored 84.1% (very feasible).  Conclusion: The developed E-report card application is suitable for use in the field to assist technically in the implementation of SDIDTK at the PAUD unit level and to help increase the coverage of children receiving growth and development monitoring